ROLE OF Si AT A LOWER LEVEL ON THE MECHANICAL PROPERTIES OF Al-BASED AUTOMOTIVE ALLOY - Khan, Akib Abdullah; Hossain, Al-Kabir; Kaiser, Mohammad Salim (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Silicon effect at a lower level around 3.5 wt% on the tensile, impact, and fracture properties of Al-based automotive alloys has been investigated through T6 heat treatment. The results demonstrate that tensile strength increases in the aged alloys mainly due to development of Al2Cu and Mg2Si precipitates inside the Al-matrix. Higher Si-added alloy shows higher strength through Si-rich precipitates and hinders the true strain at tensile behaviour. The alloys ductility decreases with treatment temperature in favour of GP zones, βʹʹ, βʹ, β precipitates formation plus Qʹʹ phase and finally increases for precipitates coarsening. Microstructural study confirms the coarse grain boundary and plate-like eutectic phase when Si is added. Fractography shows a small dimple structure from the Al dendrites and the crack initiates through brittle Si-rich particles.
Keywords: Automotive Al- alloy; T6 heat treatment; true stress-strain; impact strength; fractography